The Effectiveness of Using a Modified “Beat Frequent Pick” Algorithm in the First International RoShamBo Tournament - Fernandez, Proceso L, Jr (Archīum Ateneo, 2015)
In this study, a bot is developed to compete in the first International RoShamBo Tournament test suite. The basic “Beat Frequent Pick (BFP)” algorithm was taken from the supplied test suite and was improved by adding a random choice tailored fit against the opponent's distribution of picks. A training program was also developed that finds the best performing bot variant by changing the bot's behavior in terms of the timing of the recomputation of the pick distribution. Simulation results demonstrate the significantly improved performance of the proposed variant over the original BFP. This indicates the potential of using the core technique (of the proposed variant) as an Artificial Intelligence bot to similarly applicable computer games.